Challenging the difference between white and brown Agaricus bisporus mushrooms: Science behind consumers choice. Issue 6 (4th June 2018) - Vunduk, Jovana; Djekic, Ilija; Petrović, Predrag; Tomašević, Igor; Kozarski, Maja; Despotović, Saša; Nikšić, Miomir; Klaus, Anita
Abstract : Purpose: The purpose of this paper is to examine compositional differences between brown and white varieties of Agaricus bisporus during shelf life and to determine if the growing demand for the brown variety is scientifically justified. Design/methodology/approach: Field research enabled analyzing consumers' perceptions on intrinsic, extrinsic and quality characteristics of mushrooms. A total of 275 consumers participated in the survey. Obtained results were used for comparing white and brown varieties of A. bisporus over a period of 22 days. Mushrooms were packed in air and in modified atmosphere packaging (MAP) at 4°C. Samples were analyzed for their nutritional, antioxidative and microbiological characteristics. Findings: Two weeks from harvest, white variety showed higher amount of essential nutrients, while during the third week, brown mushrooms were more nutritionally valuable. Brown variety had better antioxidative ability for all 22 days of storage. Aerobic plate count (APC) was as expected for the mushrooms. MAPs significantly lowered APC in both varieties. The number of Enterobacteriaceae was equal for both varieties at the beginning, but later on they developed much faster in the case of brown variety. Field research combined with specific analyses clarified that there are no nutritive or microbiological reasons for the precedence of brown variety over white. Research limitations/implications: Sensory aspect of the quality of mushrooms was not analyzed. Originality/value: Market trend toward brown variety was scientifically challenged.